2014
DOI: 10.1097/mnm.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

Radioguided parathyroidectomy in patients with secondary hyperparathyroidism due to chronic renal failure

Abstract: Radioguided localization of the parathyroid glands improves the success rate of surgery in patients with CRF undergoing parathyroidectomy for sHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…The use of injecting Technetium 99-m as a radioisotope to help localize and confirm hyperfunctioning parathyroid tissue has become a popularly used intraoperative adjunct in PTX for PHPT as described in the AAES guidelines for PHPT 1. Use of the Technetium 99-m and the radioguidance probe can facilitate identification of hyperfunctioning parathyroid glands including those in ectopic locations and has been shown to decrease overall operative time 384–386. Use of the “>20% ex vivo count” rule also identifies both hyperplastic and adenomatous parathyroid glands with high sensitivity, and has been suggested as a reliable substitute for frozen section analysis 337,366,387…”
Section: Other Intraoperative Adjuncts and Nonsurgical Approachesmentioning
confidence: 99%
“…The use of injecting Technetium 99-m as a radioisotope to help localize and confirm hyperfunctioning parathyroid tissue has become a popularly used intraoperative adjunct in PTX for PHPT as described in the AAES guidelines for PHPT 1. Use of the Technetium 99-m and the radioguidance probe can facilitate identification of hyperfunctioning parathyroid glands including those in ectopic locations and has been shown to decrease overall operative time 384–386. Use of the “>20% ex vivo count” rule also identifies both hyperplastic and adenomatous parathyroid glands with high sensitivity, and has been suggested as a reliable substitute for frozen section analysis 337,366,387…”
Section: Other Intraoperative Adjuncts and Nonsurgical Approachesmentioning
confidence: 99%
“…In recent years, parathyroid surgery has undergone a great evolution with the use of minimally invasive techniques and heat-sealing devices [ 15 , 16 ]. However, surgery is still thought to be associated with more complications than oral medication.…”
Section: Introductionmentioning
confidence: 99%
“…However, in studies of parathyroid hyperplasia secondary to chronic renal disease, RNP use was shown to retain its utility and improve the success of surgery. 15, 16 We believe RNP should behave similarly for parathyroid hyperplasia in pHPT. In a study of 845 patients treated with focused parathyroidectomy guided by IOPTH monitoring, the authors concluded that it was the inability of the surgeon to find the abnormal parathyroid gland (rather than missed MGD) that led to operative failure.…”
Section: Discussionmentioning
confidence: 88%